Common Distribution of gad Operon in Lactobacillus brevis and its GadA Contributes to Efficient GABA Synthesis toward Cytosolic Near-Neutral pH - Wu, Qinglong; Tun, Hein Min; Law, Yee-Song; Khafipour, Ehsan; Shah, Nagendra P. (Frontiers in Microbiology, 2017)
Many strains of lactic acid bacteria (LAB) and bifidobacteria have exhibited strain-specific capacity to produce γ-aminobutyric acid (GABA) via their glutamic acid decarboxylase (GAD) system, which is one of amino acid-dependent acid resistance (AR) systems in bacteria. However, the linkage between bacterial AR and GABA production capacity has not been well established. Meanwhile, limited evidence has been provided to the global diversity of GABA-producing LAB and bifidobacteria, and their mechanisms of efficient GABA synthesis. In this study, genomic survey identified common distribution of gad operon-encoded GAD system in Lactobacillus brevis for its GABA production among varying species of LAB and bifidobacteria. Importantly, among four commonly distributed amino acid-dependent AR systems in Lb. brevis, its GAD system was a major contributor to maintain cytosolic pH homeostasis by consuming protons via GABA synthesis. This highlights that Lb. brevis applies GAD system as the main strategy against extracellular and intracellular acidification demonstrating its high capacity of GABA production. In addition, the abundant GadA retained its activity towards near-neutral pH (pH 5.5-6.5) of cytosolic acidity thus contributing to efficient GABA synthesis in Lb. brevis. This is the first global report illustrating species-specific characteristic and mechanism of efficient GABA synthesis in Lb. brevis.